Bhānubhakta smāraka grantha : mrtyu bhaeko 70 varsha pugekā upalakshyamā prakāśita - Jñavālī, Sūryavikrama (Nepāli Sāhitya Sammelana, 1940)
Commemoration volume on Bhānubhakta, 1812-1868, Nepali poet; comprises articles on his works.